A study on dampness defect in government quarters in three different areas (urban, coastal and highland) / Mohammad Faiz Ab Halim - Ab Halim, Mohammad Faiz (Faculty of Architecture, Planning and Surveying, 2013)
Dampness is one of the defects that commonly occur at all types of building. The dampness defect is usually causes by the excessive quantity of moisture of moisture inside the building. It will cause a bad internal and external environment condition which can lead to building deterioration. This study will be describe on the dampness defect that occurs at the government building in three different area which is Shah Alam (Urban), Kuantan (Coastal) and Cameron Highlands (Highland). The purpose of this study is to investigate the causes of dampness that occur at each area selected and to compare the characteristics of the dampness defect based on visual inspection. This study focused at the government quarters at different areas where the weather condition of each area probably lead to different causes and types of dampness defect. From the analysis of dampness defect at the three areas that has been carried out, the type of dampness that is occurs is different at each area. The most dampness defect occurs at the urban is mold growth. However, there is a dampness defect that that only occurs at coastal area which is hygroscopic salt. And the most dampness defect occur at highland area is mold growth and discolouration. The dampness problems at each area need a remedial and repairing work such as removing of the mold growth. All the building needs a proper maintenance in order to maintain the condition and performance of the building.